REACTION MODEL TO PREDICT THE THERMAL DEGRADATION MECHANISM OF POLYPROPYLENE – CARBON NANOTUBE COMPOSITE - ., Alauddin; Khan, Azhar; Ahmad, Imran (Universitas Mataram, 2020)
The degradation of polymer is known, but the effect of CNT composite is the less studied concept. In this article, the effect of CNT on degradation is presented. The first stage involved a literature study for reaction mechanisms in oxidative thermal degradation of Polypropylene (PP). A reaction model is then developed by considering mass balance on various reactive species. Literature is reviewed to find or estimate the model parameters. The parameters not found in the literature are fitted. The model equations are solved after assuming initial conditions and values of various parameters. After the PP polymer degradation modeling comparison drown between PP and PP/MWCNT composite by making a hypothesis based on Arrhenius equations (activation energy increases, the rate constant decreases, and therefore the rate of reaction decreases). The result shows that the CNT composite takes much time to degrade as compared to the polymer.